Effect of phototherapy with alumunium foil reflectors on neonatal hyperbilirubinemia - Tony Ijong Dachlan; Tetty Yuniati; Abdurachman Sukadi (Indonesian Pediatric Society, 2015)
Background Neonatal hyperbilirubinemia (NH) is one of the most common problems in neonates, but it can be treated with blue light phototherapy. Developing countries with limited medical equipment and funds have difficulty providing effective phototherapy to treat NH, leading to increased risk of bilirubin encephalopathy. Phototherapy with white reflecting curtains can decrease the duration of phototherapy needed to reduce bilirubin levels. Objective To compare the duration of phototherapy needed in neonates with NH who underwent phototherapy with and without aluminum foil reflectors. Methods This open clinical trial was conducted from July to August 2013 at Dr. Hasan Sadikin Hospital, Bandung, Indonesia. The inclusion criteria were term neonates with uncomplicated NH presenting in their first week of life. Subjects were randomized into two groups, those who received phototherapy with or without aluminum foil reflectors. Serum bilirubin is taken at 12th, 24th, 48th hours, then every 24 hours if needed until phototherapy can be stopped according to American Academy of Pediatrics guidelines. The outcome measured was the duration of phototherapy using survival analysis. The difference between the two groups was tested by Gehan method. Results Seventy newborns who fulfilled the inclusion criteria and had similar characteristics were randomized into two groups. The duration of phototherapy needed was significantly less in the group with aluminum foil reflectors than in the group without reflectors [72 vs. 96 hours, respectively, (P<0.01)]. Conclusion The required duration of phototherapy with aluminum foil reflectors is significantly less than that of phototherapy without reflectors, in neonates with NH.